Measuring Service Gap of Banking services in Bangladesh- A Study Based on Selected Private Commercial Bank in the Northern Region (Global Journal of Management and Business Research, 2021)
This research investigates the service gap between client's expectation and perception regarding banking services in Bangladesh with a particular focus on the SERVQUAL model along with the five dimensions: Tangibility, Reliability, Responsiveness, Assurance, and Empathy. We investigate the dimensions of quality of banking service and its impact on customer satisfaction. A self-administered and structured questionnaire use to collect data from 200 respondents of banks' clients. The SPSS software use here for analyzing data. Different statistical tools use which are compatible with our research, such as factor analysis, reliability analysis, and hypothesis testing. We survey twenty private commercial banks. Average of ten customers take as a sample from each bank. As for clients' perception, the services gap (Expected service -Perceived service), in the dimensions of reliability, responsiveness, and empathy, is significant because expected service is below perceived service in the private banks in the northern region of Bangladesh.
Keywords: servqual; service gap; tangibility; reliability; responsiveness